2009
DOI: 10.5296/rae.v1i1.301
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Gold Prices, Gold Mining Stock Prices and Stock Market Prices Comovements

Abstract: We examine the dynamic relationships between gold prices, stock price indices of gold mining companies and broad stock market indices. Evidence of cointegration between these variables is found. A vector error-correction model reveals that both gold and large-cap stock prices adjust to disturbances to restore the long-term relationship between the variables. Short-term unidirectional causal relationships are running from large-cap stock prices to gold mining company stock prices and from gold mining company st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 14 publications
2
23
0
Order By: Relevance
“…Moreover, Gilmore et al (2009) use co-integration tests and a vector-error correction (VEC) model to examine the dynamic relationship between gold price, stock indices of gold mining companies and broad stock market indices. The research based on VEC model reveals that both gold and large capitalization stock prices tend to restore the long-term equilibrium following shocks to the variables, with the gold price adjusting more rapidly.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, Gilmore et al (2009) use co-integration tests and a vector-error correction (VEC) model to examine the dynamic relationship between gold price, stock indices of gold mining companies and broad stock market indices. The research based on VEC model reveals that both gold and large capitalization stock prices tend to restore the long-term equilibrium following shocks to the variables, with the gold price adjusting more rapidly.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yahyazadehfar and Babaie (2012), and Le and Chang (2012) found significant relationship between stock market prices and gold prices and state that stock market is a reason for increasing gold rate. Gilmore et al (2009) There is apparent evidence that in turbulent periods with economic uncertainty, as equity prices fall gold price rises and attention focuses on gold as a safe haven.…”
Section: Oil Price Versus Stock Pricesmentioning
confidence: 99%
“…Claire, Ginette, Rajneesh and Ahmet [8] in this paper they are trying to expose that impact of macroeconomic variables on the Korea stock exchange and for this purpose they have used the cointegration and causality test. Their results have shown that there is short run relationship between them.…”
Section: Literature Reviewmentioning
confidence: 99%